PENGARUH TEMAN SEBAYA DENGAN PERILAKU MEROKOK ELEKTRIK PADA SISWA MADRASAH ALIYAH DI KOTA JAMBI - delfia dwi ananta; M. Ridwan S.K.M.,M.PH; M.Rifki Azhary M.K.M; Puspita Sari S.KM.,M.Kes (Jurnal Penelitian Kesmasy, 2026)
Abstract Electronic smoking (vaping) behavior among teenagers is a new phenomenon in the field of public health that continues to increase throughout the world. E-cigarettes or vapes are increasingly popular among adolescents due to the misconception that they are safer than conventional cigarettes, despite having similar or even higher health risks. This study aims to the influence of peers on e-cigarette smoking behavior among Madrasah Aliyah students in Jambi City. E-cigarettes or vapes are increasingly popular among adolescents due to the misconception that they are safer than conventional cigarettes, despite having similar or even higher health risks. This study employed a cross-sectional design and a quantitative methodology. 167 pupils from 15 Jambi City schools made up the sample, which was chosen at random. A structured questionnaire that had undergone validity and reliability testing was used to gather data. The Chi-Square test was used to analyze the data. The results revealed significant relationships peer influence (p=0.000; OR=4.117), indicating that students influenced by their peers were four times more likely to use e-cigarettes than those who were not. Peer influence plays a crucial and dominant role in shaping e-cigarette smoking behavior among MA students in Jambi City. School-based interventions and peer-led education programs are essential to reduce e-cigarette use among adolescents.